Perancangan Sistem Informasi Manajemen Dokumen Pada Kelurahan Keagungan - Muhammad Achirudin; Eva Zuraidah (STMIK Budi Darma, 2022)
Letters are a bridge of understanding and communication tools for one person and another. In Kelurahan Keagungan, document management has not been done computerized. The process will experience obstacles such as a lot of paper required. This relates to the security of the letter or information stored because if it is not managed properly the paper can be damaged or lost. The purpose of this research is to build a website-based document management information system. Before creating a system, the author makes several UML diagrams such as Use Case Diagrams, Activity Diagrams, Class Sequence Diagrams, Component Diagrams and Deployment Diagrams. The development method used is the RAD (Rapid Application Development) model where the software development process model is classified as a multilevel technique. This method emphasizes a short, concise and fast development cycle. This information system uses the PHP and MYSQL programming languages ??as its database. This information system was created to make it easier for each incoming and outgoing mail data search quickly, and a solution for the Keagungan Village who needs a web-based information system that can speed up the work in archiving incoming and outgoing letters.